RELATIONSHIP BETWEEN BREAKFAST AND THE LEVEL OF ANXIETY ON GRADE 6 FEMALE STUDENTS OF PATRANG III, IV, AND V PUBLIC ELEMENTARY SCHOOL JEMBER WHEN EXPERIENCING MENARCHE - Annisa Nurida; Sujono Kardis; Eva Rosita Dewi (PROCEEDING UMSURABAYA, 2023)
The purpose of this study is to see whether there is a relationship between breakfast and the level of anxiety on the female students when they experience menarche.The design of this study was quantitative correlation with cross sectional data collection. The sample was taken by using "purposive sampling" of 24 female students, while the data was analysed by using chi square.The result of the study is P = 0.006 so that P < 0.05 which means that there is a significant relationship between breakfast and the level of anxiety on the female students of grade 6 elementary school who experience menarche. It shows that breakfast can reduce the level of their anxiety. Girls who will step into adolescence are characterised by menarche, and this change is one of the triggering factors for anxiety. There is a significant relationship between breakfast and the level of anxiety on female students in Patrang III, IV and V Public Elementary School when experiencing menarche.Keywords: tryptophan, tyrosine, serotonin, noreephinnefrin, anxiety.